PENYELESAIAN ITSBAT NIKAH PASCA PEMBAHARUAN UNDANG-UNDANG PERKAWINAN DI PENGADILAN AGAMA MUARA SABAK - Fitria Wahyu Ningrum; Hermanto Harun; Fuad Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the study was to obtain empirical data on the completion of itsbat nikah before and after the reform of the Marriage Law. The research uses a mixed method that combines quantitative approaches based on numbers and statistics and qualitative approaches based on narrative and description. The approach used is legal sociology and saddu al-dzariyah with a utilitarianism paradigm. Primary data sources include the Chairperson, Registrar, Judges, Information Officer at the Muara Sabak Religious Court, KUA, and the community of East Tanjung Jabung Regency. Secondary data are scientific books, journals, decisions, case statistics, and annual reports. Data collection techniques were conducted through questionnaire surveys and analysis of case results with method triangulation techniques to test the validity of the data. The results showed that: (1) People in Muara Sabak have a positive view of marriage regulations and increasingly realize the importance of marriage registration. However, understanding of itsbat nikah still varies, influenced by educational factors and access to information. Marriage practices remain influenced by culture, tradition and socio-economic conditions affect the decision to marry. (2) The pre- and post-reform isbat nikah mechanisms show that although the basic mechanism has not changed significantly, there have been improvements in the requirements and stricter procedures to ensure the validity of marriages. The Constitutional Court's decision expanding the scope of isbat nikah has also had an effect on the recognition of the rights of children from unregistered marriages. (3) Regarding the space for judges in responding to isbat nikah applications, there is flexibility and adaptation in legal practice in the Religious Courts. After the reform of the Marriage Law, judges were given more room to exercise “ijtihad” in assessing applications for isbat nikah, including for marriages performed after the enactment of the law, thus reflecting the court's efforts to meet the community's need for legal certainty regarding marital status.